Exhaled breath condensate as a biomonitor for metal exposure: a new analytical challenge - Barreiros, M. Alexandra (2013)
The study of exhaled breath condensate (EBC) obtained by cooling exhaled air under conditions of spontaneous breathing is considered one of the areas with higher interest in respiratory health research. The use of EBC for elemental determination in occupational exposure requires a standard methodological procedure to implement its practice in occupational studies. EBC is an inhomogeneous sample with organic and particulate matter in suspension, which may hamper analytical results reliability. Total reflection X-ray fluorescence and inductive coupled-plasma mass spectrometry (ICP-MS) techniques were chosen as both are multielemental, require small sample volumes and have appropriate detection limits. Estimation of the overall uncertainty in both techniques was carried out using a pool of EBC collected from a group of workers of a lead processing industry to perform precision and trueness studies for K, Mn, Cu, Cd, Sb and Pb. Precision was estimated in terms of repeatability using the native EBC sample pool and trueness in terms of recovery obtained from spiking aliquots of the EBC pool with K, Mn, Cu, Cd, Sb and Pb at different concentrations. Recovery was the most significant contribution to total uncertainty. The overall uncertainties obtained for ICP-MS enabled to discriminate between groups of individuals exposed to different levels of contaminants. Therefore EBC proved to be useful in human biomonitoring.